2019
DOI: 10.1038/s41598-019-43349-6
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution scintillator dosimetry of synchrotron microbeams

Abstract: Microbeam radiation therapy is a novel pre-clinical external beam therapy that uses high-brilliance synchrotron X-rays to deliver the necessary high dose rates. The unique conditions of high dose rate and high spatial fractionation demand a new class of detector to experimentally measure important beam quality parameters. Here we demonstrate the highest spatial resolution plastic scintillator fibre-optic dosimeter found in the literature to date and tested it on the Imaging and Medical Beam-Line at the Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…This method has shown good agreement with radiochromic film, however the measurements are acquired point by point and therefore the shape of the profiles are not shown instantaneously which limits its use for in vivo dosimetry or in situ verification. The same applies to the use of scintillating fibers, as shown by Archer et al …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This method has shown good agreement with radiochromic film, however the measurements are acquired point by point and therefore the shape of the profiles are not shown instantaneously which limits its use for in vivo dosimetry or in situ verification. The same applies to the use of scintillating fibers, as shown by Archer et al …”
Section: Introductionmentioning
confidence: 84%
“…18 This method has shown good agreement with radiochromic film, 19 however the measurements are acquired point by point and therefore the shape of the profiles are not shown instantaneously which limits its use for in vivo dosimetry or in situ verification. The same applies to the use of scintillating fibers, as shown by Archer et al 20 Various groups have developed silicon strip detectors capable of quantifying parameters of the microbeam field. [21][22][23] Whilst hybrid strip detectors (with separate sensor and readout) can offer greater resistance to radiation than monolithic pixelated detectors, strip detectors do not provide detailed information about the 2D profile of the radiation field and, therefore, will be more sensitive to angular misalignment.…”
Section: B Current Verification Methodsmentioning
confidence: 94%
“…5 a, upper). Initial use of the accelerator was in conjunction with a wiggler to generate electromagnetic energy similar to ESRF and IMBL (Table 1 ), but delivered 2 GW at 140 GHz mm-wave energy for fusion research studies 21 , 22 , 62 . Because of the pulse width requirement that was based on an older design, the machine gradient was only < 0.5 MV m −1 .…”
Section: Resultsmentioning
confidence: 99%
“…For point measurements, the setup usually consists of a small scintillator coupled to an optical fiber and a photodetector. Recently, Archer et al [93] demonstrated the use of miniature BG400 plastic scintillator (10 µm thick) coupled to a fiber optic and a SiPM for dosimetry at the Imaging and Medical Beam-Line at the Australian Synchrotron with an average dose-rate of 4,435 Gy/s, resolving beams of 50 µm width.…”
Section: Scintillatorsmentioning
confidence: 99%